Tropical Cyclone Track and Intensity Predictability - Doyle, J.; Reynolds, C.; Amerault, C.; Goerss, J.; McLay, J.; Hodur, R. M. (2010 DoD High Performance Computing Modernization Program Users Group Conference, 2010)
Atmospheric ensemble and ad joint systems can provide valuable insight into the practical limitations of our ability to predict the path of tropical cyclones and their strength. An ensemble forecast system can be used to address tropical cyclone forecast uncertainty. An ad joint model can be used for the efficient and rigorous computation of numerical weather forecast sensitivity to changes in the initial state. The sensitivity calculations illustrate complex influences on tropical cyclone evolution that occur over a wide range of scales from convective clusters to larger scale weather systems. Rapid growth of small perturbations can lead to errors on multiple scales that conspire to limit the forecast accuracy of the path and intensity of tropical cyclones. Inherent uncertainties in tropical cyclone forecasts motivate the need for development of ensemble prediction systems that can provide probabilistic forecast guidance for tropical cyclones. New capabilities have been developed for the Navy's global weather ensemble forecast system including a high-resolution system and new methods for perturbing the initial state.